The right to be parents : LGBT families and the transformation of parenthood - Ball M., Carlos A. (New York : New York University Press, 2016)
This publication provides a detailed history of how LGBT parents have turned to the courts to protect and defend their relationships with their children. Ball chronicles the stories of LGBT parents who have fundamentally changed how American law defines and regulates parenthood.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: Parent and child -- United States; Gay parents -- Legal status, laws, etc. -- United States; Custody of children -- United States; Law; LGBTQ+ Interest; United States of America, USA; Gay & Lesbian studies; Sociology: family & relationships; Private or civil law: general; Family law: same-sex partnership